Capacity building of resource-poor farmers in paddy-wheat cum dairy production systems through Farmer FIRST Programme under irrigated agro-eco region of Haryana - Sankhala, Gopal; Chahal, V P; Kumar, Sunil (Indian Farming, 2022)
.